The work of Raimund Abraham - Frampton, Kenneth
Se analizan varias obras del arquitecto. Contiene: Monument to a Fallen Building, 1981. The Church on the BerlinWall, 1984. Times Theater Tower, 1984. Projects for Biennale Architettura Venezia, 1985. Projects for the International Building Exhibition Berlin, 1981-86.
Keywords: ABRAHAM, RAIMUND; ALEMANIA; BERLIN; MONUMENTOS; ARQUITECTURA RELIGIOSA; IGLESIAS; TORRES; TEATRO; SALAS DE ESPECTACULOS; PROYECTOS; EDIFICIOS DE VIVIENDAS